Bold policy changes are needed to meet the need for organ transplantation in India. Issue 9 (23rd February 2021) - Shroff, Sunil; Gill, John S.
Abstract : Twenty‐five years after India passed legislation to legalize brain death, deceased donor transplantation remains underdeveloped while the country has established formidable capacity for living donor transplantation. Because of a large number of potential deceased donors, there is hope that deceased donation could help meet India's enormous need for organ transplantation. However, significant policy and practical barriers limit progress. The vast majority of potential deceased donors are poor motor vehicle accident victims who present for care in hospitals without the necessary infrastructure or expertise to support deceased donation. In contrast, transplant infrastructure and expertise are concentrated in private hospitals and are only accessible to those with the ability to pay. Given these realities, the potential of deceased donor transplantation can only be recognized if Indians who are likely to donate organs are also provided access to transplantation. In this viewpoint, we review the current status of organ transplantation in India and propose new policies to establish a national organization to oversee deceased donor services in all states, to fund resources needed to support deceased donation, to leverage the existing living donor infrastructure to advance deceased donor transplantation, and call for establishment of government policy on funding for posttransplant care and immunosuppression. Abstract : This viewpoint proposes policies to leverage India's formidable capacity for living donor transplantation to advance deceased donation and provide equitable access to organ transplantation for its citizens.